PERAN KELOMPOK MASYARAKAT â€PANTAI NUNSUIâ€ DALAM KEBERLANJUTAN PENGELOLAAN WILAYAH PESISIR TAMAN WISATA ALAM LAUT (TWAL) TELUK KUPANG - Lebrina Ivantry Boikh; Jhon Septin Mourisdo Siregar; Maharani (Techno-Fish, 2023)
In managing the TWAL of Kupang Bay, synergy and participation of the surrounding community are needed to maintain and preserve the existing coastal and marine resources. The presence of the "Nunsui Beach" Community Group is expected to be able to contribute to efforts to sustain coastal and marine resources in TWAL Teluk Kupang. This study aims to determine the role of the community, especially the "Nunsui Beach" community group in the sustainable management of the TWAL Teluk Kupang coastal area. The research was conducted in the Oesapa Village, Kelapa Lima District, Kupang City with the main focus being the "Nunsui Beach" Community Group. Source of data is done by using a questionnaire method with a questionnaire instrument. This research use desciptive qualitative approach. The TWAL Teluk Kupang Community Group â€œNunsui Beachâ€ is a group that was legalized through Decree of the Oesapa Village Head No. 011/SKEP/KOSP/2020 concerning the establishment of the â€œNunsui Beachâ€ group, Oesapa Village, Kelapa Lima District, Kupang City. This group is engaged in capture fisheries activities using fishing rods, trawls, fixed nets and floating nets and is tasked with efforts to improve the welfare of the group, develop the creative economy and help and support conservation efforts carried out by the KSDA Center in the TWAL area of Kupang Bay. The role of the "Nunsui Beach" Community Group in implementing sustainable management, namely carrying out independent and joint patrols with the Government (NTT BKSDA), collecting data on catches, participating in developing the creative economy through selling processed catches and local culinary snacks and conveying and implementing applicable fishing regulations and delivery of useful information to improve the human resources of the Oesapa Village.